The Temporal pathological changes of venous catheter-related fibrin sheath and their implications for nursing practice - Wenshuai Tang; Limei Deng; Haimin Qin (PLoS ONE, 2025)
Background To investigate the time-sequential variation patterns of the impact of venous catheter-related fibrin sheath (FS) on blood vessels during the ultra-early period (12 hours to 4 days) after catheterization, and provide a basis for optimizing clinical catheter management strategies. Methods A rabbit ear marginal vein indwelling catheter model (n = 40) was established and randomly divided into 12h, 1d, 2d, 3d, and 4d indwelling groups (8 rabbits per group). After sampling, Hematoxylin-Eosin ( HE ) staining was performed to systematically evaluate infusion patency, FS thickness, FS structural integrity, thrombus area, inflammatory cell infiltration, and venous edema. Welch’s ANOVA, trend tests, and Spearman correlation analysis were used for data analysis. Results The patency of the catheters decreased significantly with increasing indwelling time (p < 0.001), with the rate dropping from 87.5% at 12 hours to 0% at 4 days, accompanied by a complete blockage rate of 75.0% at the latter time point. Concurrently, the thrombus area exhibited an extremely significant increase (p < 0.001), from 0.12 ± 0.03 mm² at 12h to 1.86 ± 0.20 mm² at 4 days (η² = 0.976). Regarding the fibrin sheath (FS), its thickness increased extremely significantly (p < 0.001) from 23.5 ± 4.2 μm at 12h to 156.7 ± 10.8 μm at 4 days (η² = 0.986). Furthermore, the integrity of the FS improved over time (p < 0.001), shifting from a state of predominantly incomplete continuity (87.5%) at 12h to predominantly complete continuity (87.5%) at 4 days.The inflammatory response intensified markedly, with the inflammatory cell count significantly increasing from 12.3 ± 2.5 cells/field at 12h to 85.4 ± 6.3 cells/field at 4 days (p < 0.001). The proportion of samples exhibiting severe inflammation rose from 0% to 62.5% (p < 0.001). Similarly, the degree of venous edema worsened significantly (p < 0.001), shifting from predominantly mild edema (62.5%) at 12h to severe edema (62.5%) at 4 days.Key time nodes were identified: 48 hours represented a critical point, characterized by a thrombus area >0.75 mm², FS thickness >78 μm, and a prevalence of moderate-to-severe inflammation and edema exceeding 75%. By 72 hours, a high-risk point was observed, marked by a complete blockage rate >50%, severe edema >25%, and FS complete rupture >50%. Conclusion FS rapidly forms and dynamically evolves during the ultra-early period after catheterization, leading to time-dependent exacerbation of mechanical obstruction, thrombosis, and vascular inflammatory injury. The study identifies 48–72 hours as a critical intervention window, recommending enhanced clinical assessment and timely intervention (e.g., optimizing catheter replacement timing) to reduce the risk of catheter-related complications.